Advanced blowout & well control - Grace, Robert D. (Gulf Pub. Co., 1994)
In petroleum industry drilling operations even the most simple blowout can kill people and cost millions of dollars in equipment losses - and millions more in environmental damage and ensuing litigation. Government environmental and safety requirements demand that operating companies and drilling contractor personnel be rigorously trained in well control procedures and in responding to blowouts when they occur. The book reviews classical pressure control procedures. In addition, specific situations are presented along with detailed procedure to analyze alternatives and tackle problems. The use of fluid dynamics in well control, which the author pioneered, is given careful treatment, along with many other topics such as relief well operations, underground blowouts, slim hole drilling problems, and special services such as fire fighting, capping, and snubbing. Case histories are presented, analyzed, and discussed.